Profiles of academic and cognitive abilities differ in younger and older children from diverse socioeconomic neighbourhoods - Frank D. Baughman; Sally A. Cook; Simone K. Treasure; Amy Morley; Evan Dauer; Darren Haywood (Australian Journal of Psychology)
Objective Research indicates that socioeconomic status (SES) influences developmental outcomes, particularly in language, executive functions, and intelligence, though findings have been mixed. This study examines the relationship between academic, cognitive and intellectual abilities in a cross-section of children at two age levels in low-SES vs. high-SES schools.Method We administered a computerised battery of tests to 46 children in Grade Two (youngest 6.9 years old) and 67 children in Grade Six (oldest 12.4 years old) across four primary schools from low-SES and high-SES neighbourhoods. The test battery comprised two academic ability tests, five cognitive ability tests, and two intelligence tests.Results In Grade Two, the low-SES group showed disadvantages on all measures except the Wisconsin Card Sorting Task and Choice Reaction Time. In Grade Six, while academic differences persisted between SES groups, cognitive differences were limited to the Wisconsin Card Sorting Task, where the high-SES group performed better than the low-SES group.Conclusions Though our results pertain to cross-sectional data using neighbourhood indices of SES, our findings contrast with previous research showing broad and pervasive disadvantages associated with lower SES. Future research should further examine the potential differences and similarities in developmental outcomes across SES groups using longitudinal methods.